'Better understanding about what's going on': young Australians' use of digital technologies for health and fitness. Issue 1 (2nd January 2020) - Lupton, Deborah
ABSTRACT: Digital technologies such as websites, online discussion forums, social media, content-sharing platforms, mobile apps and wearable devices are now available as a means for young people to learn about and promote their health, physical fitness and wellbeing. This article provides findings from a qualitative interview-based study of young Australians (aged 16–25 years) which explored their practices and understandings related to digital and non-digital sources of health and fitness information, advice and support. The interviews were analysed using a feminist new materialist theoretical framework, paying attention to the affordances, relational connections and affective forces gathering in human-nonhuman assemblages to create a set of key agential capacities. The agential capacities generated by the participants' enactments of digital health included gaining a better knowledge of bodies, illness and healthcare and feeling more in control of health and wellbeing states. While the affordances of convenience, accessibility and detail and diversity of information offered by digital media and devices were valued by the participants, their accounts also highlighted the importance of face-to-face as well as online relationships and personal connections with other people for providing information and support, including family members and friends as well as medical professionals. The participants highly valued the agential capacity of digital technologies to generate detailed information about their bodies and health states and imagined new technologies that would be able to achieve even more detailed personalisation and customisation. However, they expressed little knowledge or concern about how their personal health data may be exploited by other actors or agencies. These insights go some way to recognising and acknowledging the embodied, affective and relational dimensions of living with, through and in the more-than-human worlds of digital health.